Polycaprolactone electrospun fiber scaffold loaded with iPSCs-NSCs and ASCs as a novel tissue engineering scaffold for the treatment of spinal cord injury - Zhou X (Dove Medical Press, 2018)
XianHu Zhou,1,2* GuiDong Shi,1,2* BaoYou Fan,1,2 Xin Cheng,1,2 XiaoLei Zhang,1,2 Xu Wang,1,2 Shen Liu,1,2 Yan Hao,1,2 ZhiJian Wei,1,2 LianYong Wang,3 ShiQing Feng1,2 1International Science and Technology Cooperation Base of Spinal Cord Injury, Department of Orthopedic Surgery, Tianjin Medical University General Hospital, Tianjin, People’s Republic of China; 2Tianjin Neurological Institute, Key Laboratory of Post-Neuroinjury Neuro-repair and Regeneration in Central Nervous System, Ministry of Education and Tianjin City, Tianjin, People’s Republic of China; 3Key Laboratory of Bioactive Materials, Ministry of Education, College of Life Sciences, Nankai University, Tianjin, People’s Republic of China *These authors contributed equally to this work Background: Spinal cord injury (SCI) is a traumatic disease of the central nervous system, accompanied with high incidence and high disability rate. Tissue engineering scaffold can be used as therapeutic systems to provide effective repair for SCI. Purpose: In this study, a novel tissue engineering scaffold has been synthesized in order to explore the effect of nerve repair on SCI. Patients and methods: Polycaprolactone (PCL) scaffolds loaded with actived Schwann cells (ASCs) and induced pluripotent stem cells -derived neural stem cells (iPSC-NSCs), a combined cell transplantation strategy, were prepared and characterized. The cell-loaded PCL scaffolds were further utilized for the treatment of SCI in vivo. Histological observation, behavioral evaluation, Western-blot and qRT-PCR were used to investigate the nerve repair of Wistar rats after scaffold transplantation. Results: The iPSCs displayed similar characteristics to embryonic stem cells and were efficiently differentiated into neural stem cells in vitro. The obtained PCL scaffolds were ~0.5 mm in thickness with biocompatibility and biodegradability. SEM results indicated that the ASCs and (or) iPS-NSCs grew well on PCL scaffolds. Moreover, transplantation reduced the volume of lesion cavity and improved locomotor recovery of rats. In addition, the degree of spinal cord recovery and remodeling maybe closely related to nerve growth factor and glial cell-derived neurotrophic factor. In summary, our results demonstrated that tissue engineering scaffold treatment could increase tissue remodeling and could promote motor function recovery in a transection SCI model. Conclusion: This study provides preliminary evidence for using tissue engineering scaffold as a clinically viable treatment for SCI in the future. Keywords: induced pluripotent stem cells, polycaprolactone, spinal cord injury